2003
DOI: 10.1161/01.str.0000090350.73614.0f
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Magnetic Resonance Imaging and Transesophageal Echocardiography in Detection of Thrombus in the Left Atrial Appendage

Abstract: Background and Purpose-A noninvasive technique of visualizing the left atrial appendage (LAA) and its thrombus in patients with atrial fibrillation would be of great interest. This study examined the utility of MRI for the assessment of thrombus in the LAA. Methods-We evaluated 50 subjects with nonrheumatic continuous atrial fibrillation and a history of cardioembolic stroke.Each patient received an MRI and a transesophageal echocardiography (TEE) on the same day for thrombus detection in the LAA. Both double-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
53
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(55 citation statements)
references
References 9 publications
0
53
0
Order By: Relevance
“…The CMR can not replace the TTE or TEE in cases while the patient has undergone the implantation of CMR incompatible metallic devices, such as heart pacemaker or pacing wires. Moreover, the claustrophobia or obesity may technically limit the ability to apply this diagnostic procedure [29]. What is more, the safety issues, related to underlying renal function, have to be concerned prior to administration of gadolinium contrast agent.…”
Section: Discussionmentioning
confidence: 99%
“…The CMR can not replace the TTE or TEE in cases while the patient has undergone the implantation of CMR incompatible metallic devices, such as heart pacemaker or pacing wires. Moreover, the claustrophobia or obesity may technically limit the ability to apply this diagnostic procedure [29]. What is more, the safety issues, related to underlying renal function, have to be concerned prior to administration of gadolinium contrast agent.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the well established association between reduced LAA emptying velocities and thrombus formation in the LAA, VENC-CMR could be an attractive adjunctive non-invasive tool in this context [1,2]. A comprehensive CMR protocol including measurements of LA fibrosis, LAA dimensions and passive LAA emptying velocities could potentially improve risk stratification in patients with AF [8-11]. Furthermore, Donal et al reported a high specificity of e-wave velocities by TEE during AF to predict recovery of active LAA emptying after AF ablation [19].…”
Section: Discussionmentioning
confidence: 99%
“…Such a protocol could incorporate information on LA dimensions and function, LAA emptying, LA fibrosis as well as on aortic plaque morphology and flow characteristics to improve current risk stratification for stroke [8-13]. Second, VENC-CMR LAA flow measurements could be combined with MR angiographies of the LA and pulmonary veins that are frequently performed in clinical routine before AF ablation procedures [25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the basis of their study, Ohyama et al [45] reported that CMR correctly identified all 16 patients with thrombi on TEE, but also produced three false-positive results among 50 patients (negative predictive value, 100%; positive predictive value, 84%), with an overall agreement of K=0.88. However, identification of spontaneous echo contrast was suboptimal.…”
Section: B Amentioning
confidence: 99%